Leading through discontinuous change: A typology of problems and leadership approaches in UK boards. Issue 2 (April 2020) - Morais, Filipe; Kakabadse, Andrew; Kakabadse, Nada
Abstract: Discontinuous change and leadership behavior are subjects that have been extensively studied, but rarely from the directors' perspective. This study draws on in-depth, elite interviews with directors of large UK listed companies. It applies a grounded theory approach to data analysis, to explore how problems arising from discontinuous change influence board leadership dynamics and outcomes. The findings indicate that, when facing "wicked problems" (internal-relational or external-hostile), the chair of the board either takes the leadership role or a collaborative, joint leadership role with the CEO. When facing "tame" problems (transformational-internal or industry-external), a new CEO is often appointed to undertake an extensive diagnosis of the problem and take the lead, with the chair acting as a vigilant monitor. These findings are integrated into a typology of problems and board leadership approaches, augmenting the literature on complex problems. The study extends the application of agency and stewardship theories of board leadership by characterizing problems as contingencies that influence board leadership arrangements. It follows that regulators and boards alike should recognize the contextual nature of board leadership and leadership succession, and adopt a less prescriptive approach.